Threats to the Future of the Immigration Class Action - Jill E. Family (Washington University Journal of Law & Policy, 2008)
This Essay identifies and discusses three threats to the future of the immigration class action: (1) a general congressional willingness to restrict immigration judicial review; (2) the application of waivers of judicial review to immigration law; and (3) legislative jurisdiction-stripping attacks more specific to the immigration class action. This Essay will focus on the implications of these threats for class litigation while recognizing that these threats may also be hostile to individual litigation.
Keywords: Emigration & amp; immigration; Class action lawsuits; Due process of law; Immigration law; Judicial review; Legislative power; United States